Pengelolaan Pendidikan Anak Usia Dini (PAUD) di TK Pelangi Kota Jambi - Liza Anggraini; Eka Rianti; Muhammad Idris Addayan; Rts. Ririn Junhaniah; Desrilla Ramadani; R. Radhiah Chairunnisa; Anggi Nur Permadi; Maulan Yapi Akbar (Universitas Batanghari Jambi, 2023)
Basically the implementation of Early Childhood Education is very important in the State of Indonesia because it aims to form a complete human personality, namely to form character, character, intelligence, skills and have devotion to the Almighty God. Early Childhood Education begins with family education, this is meant to be education from parents or other parties closest to the child himself. From various educational institutions, PAUD can provide the best service for the people as well as policy makers, starting from the central government to regional governments. In this research the researcher uses qualitative research, because the researcher will try to tell and understand the facts or descriptions according to the phenomena in the field without exercising hegemony over the conditions that occur. This study aims to find out the vision, mission and goals of PAUD, to find out the management carried out by this PAUD, to find out the implementation of the programs that have been made to achieve the vision, mission and goals of PAUD. The management of PAUD in Pelangi Kindergarten is enough good. Where the kindergarten already has a clear organizational structure, the vision and mission offered are also attractive, and have reliable teachers.